Humiliation as an Emotional Driver of War Decision: Insights from Azerbaijan on the Eve of the 2020 Karabakh War - Babashov, Yahya (ADA University, 2025)
This thesis examines the influence of emotions such as humiliation and frustration on Azerbaijan’s decision to start the Second Karabakh War in 2020. Traditionally, such military conflicts are explained by strategic and political factors, but this study focuses on the emotional state of decision makers, particularly Azerbaijani President Ilham Aliyev. The main thesis is that the sense of humiliation contributed to the perception of the war as “urgent” because humiliation is experienced as an attack on national dignity, leaving military action as the only way to restore status while considering the strategic reasoning. The study is based on the concepts of Jonathan Mercer and Rose McDermott about the significance of cognitive influence of emotions on the foreign policy behavior of states. For the analysis, 18 speeches of Ilham Aliyev for the period from 2018 to 2020, a period chosen because it directly precedes the outbreak of the Second Karabakh War and it coincides with the premiership of Nikol Pashinyan, whose rhetoric and actions were repeatedly described by the Azerbaijani Ministry of Foreign Affairs as provocations. This makes the period crucial for examining how Aliyev’s emotional framing evolved in direct response to Armenia’s new leadership. Each speech was subjected to detailed analysis for the presence of statements reflecting feelings of humiliation or frustration. The intensity of these emotions was assessed on a scale from 1 to 5, based on a standardized coding rubric often used in qualitative content analysis, where 1 indicates very weak or implicit reference and 5 indicates explicit, highly emotional language. The results of the analysis showed that 72% of the president’s speeches were dominated by a sense of humiliation, with the level of this feeling increasing significantly in 2020. Frustration was also present but was less pronounced and mainly concerned failures in the negotiation process with other states. Over time, the president’s emotional state has changed: in 2018, his speeches mainly focused on a sense of humiliation, in 2019, his speeches became more controversial, and in 2020, the emphasis shifted back to a sense of humiliation, but in a much more intense form. While this variation may partly reflect strategic communication, the emotional content nevertheless indicates genuine shifts in how the conflict was framed to domestic audiences. These data indicate that it was the sense of humiliation that played a key role in the decision to go to war. Thus, this study demonstrates that emotions not only influence political decisions but can also be their main driving force. It emphasizes the need to view emotions not as secondary factors, but as integral mechanisms that help explain why leaders perceive war as a necessary and even urgent course of action.
Keywords: Emotions -- Political aspects.; Political psychology -- Influence on foreign policy.; Decision making -- Psychological aspects.; War -- Psychological aspects.; Political leadership -- Azerbaijan -- Psychological aspects.